The absence of luxS reduces the invasion of Avibacterium paragallinarum but is not essential for virulence - Li, Donghai; Huo, Caiyun; Li, Guiping; Zhu, Menghan; Xu, Fuzhou; Qiao, Jian; Sun, Huiling (Frontiers in Veterinary Science, 2024)
The contagious respiratory pathogen, Avibacterium paragallinarum, contributes to infectious coryza in poultry. However, commercial vaccines have not shown perfect protection against infectious coryza. To search for an alternative approach, this research aimed to investigate whether the quorum-sensing system of pathogens plays a crucial role in their survival and pathogenicity. The LuxS/AI-2 quorum-sensing system in many Gram-negative and Gram-positive bacteria senses environmental changes to regulate physiological traits and virulent properties, and the role of the luxS gene in Av. paragallinarum remains unclear. To investigate the effect of the luxS gene in the quorum-sensing system of Av. paragallinarum, we constructed a luxS mutant. Bioluminescence analysis indicated that the luxS gene plays a vital role in the LuxS/AI-2 quorum-sensing system. The analysis of the LuxS/AI-2 system-related genes showed the level of pfs mRNA to be significantly increased in the mutant strain; however, lsrR, lsrK, and lsrB mRNA levels were not significantly different compared with the wild type. The ability of the luxS mutant strain to invade HD11 and DF-1 cells was significantly decreased compared with the wild-type strain. In addition, all chickens challenged with various doses of the luxS mutant strain developed infections and symptoms, and those challenged with the lowest dose exhibited only minor differences compared to chickens challenged with the wild-type strain. Thus, the deletion of the luxS gene reduces the invasion, but the luxS gene does not play an essential role in the pathogenesis of A. paragallinarum.